The high prevalence of Listeria monocytogenes peritonitis in cirrhotic patients of an Egyptian Medical Center - Maysaa El Sayed Zaki; Walaa Othman El Shabrawy; Mervat M. El-Eshmawy; Shahera Aly Eletreby (Elsevier, 2011)
Summary: Background: Spontaneous bacterial peritonitis (SBP) is a potentially lethal complication of cirrhosis. It is probably the most characteristic infectious complication of cirrhosis. Aim: The aim of this study was to evaluate the bacterial and fungal causes of SBP in Egyptian population. Furthermore to predict the occurrence of rare pathogen like Listeria monocytogenes in those patients. Materials and methods: The study included 100 patients with end stage liver disease associated with ascites. Patients were suspected to have SBP. The ascitic fluids were subjected to full cytological and microbiological study. Results: The peritoneal fluid cytological study revealed that 50 samples had cell counts >250 cells/mm3. 37 samples had growth and 13 samples had no growth (CNNA). The distribution of isolated pathogens was Gram positive cocci 48.8% followed by L. monocytogenes 24.4%, Gram negative bacilli 12.2% and Mycobacterium tuberculosis 7.3. The cells counts associated with listeria culture were 475 cells/mm3 with sensitivity 70% and specificity 68%. Conclusion: The study highlights the prevalence of microorganisms in Egyptian patients with liver cirrhosis associated with ascites. It reflects the occurrence of L. monocytogenes as an important pathogen of such clinical situation. Other rare pathogens like M. tuberculosis are not uncommon in those patients. Keywords: Liver cirrhosis, SPB, MELDS score, Listeria